BONE HEALTH ASSESSMENT AND PROFILING IN CHILDREN WITH SEVERE ACUTE MALNUTRITION STUDY FROM LARKANA. : JPUMHS; 2025:15:01,57-63. http://doi.org/10.46536/jpumhs/2025/15.01.596 - Ishfaque Ahmed Mugheri1, Delijan Baloch2, Jamshed Ahmed3, Aijaz Ali Tunio4, Faryal Adnan5, Ghulam Shabir Mallah6., (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2024)
INTRODUCTION: Malnutrition in children is a significant public health and growth issue in Pakistan. Children who suffer from malnutrition are much more likely to die and suffer from illnesses. OBJECTIVE: A prospective study was conducted in a PEDS ward of Nutrition Shaikh Zaid Hospital Larkana, to determine the status of Bone Profile and associated risk factors in severe acute malnutrition in children up to 5 years of age. METHODS: A total of 105 patients with severe acute malnutrition (SAM) who were admitted to our PAEDS nutrition ward and met the inclusion criteria were included in the study, which lasted six months. Following a thorough history and examination, the patients' calcium, phosphorus, alkaline phosphatase, and vitamin D levels were assessed. RESULTS: The study examined 105 patients, mainly females, with a higher mean age and majority living in cities. Symptoms included fever, weight loss, cough, and diarrhea. Laboratory tests revealed significant biochemical imbalances, including low vitamin D levels, calcium, ALP, and phosphorus levels. These imbalances could impact health outcomes and require additional therapeutic care. The case group's vitamin D levels were significantly lower than the control group. CONCLUSION: The study found that the patient group had serious health imbalances, such as low levels of calcium, phosphorus, vitamin D, and ALP, which called for therapeutic care and focused interventions.